Ruthenium pincer-catalyzed cross-dehydrogenative coupling of primary alcohols with secondary alcohols under neutral conditions - Srimani, Dipankar; Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Ben-David, Yehoshoa; Milstein, David (Advanced Synthesis & Catalysis, 2012)
Cross-dehydrogenative coupling of primary alcohols with secondary alcohols to obtain mixed esters with the liberation of molecular hydrogen is achieved in high yield and good selectivity under neutral conditions, using a bipyridyl-based PNN ruthenium(II) pincer catalyst.

Formation of tertiary amides and H2 by dehydrogenative coupling of primary alcohols with secondary amines catalyzed by ruthenium bipyridine-based pincer complexes - Srimani, Dipankar; Balaraman, Ekambaram; Hu, Peng; Ben-David, Yehoshoa; Milstein, David (Advanced Synthesis & Catalysis, 2013)
Dehydrogenative coupling of primary alcohols with secondary amines to form tertiary amides and dihydrogen (H2) is efficiently catalyzed by bipyridyl-based ruthenium pincer complexes (0.2–1 mol%) under neutral conditions (in case of the dearomatized complexes), or with added catalytic amount of base. The reaction is sensitive to steric hindrance; in the case of amidation of bulky secondary amines a less sterically hindered complex is more efficient. Selective acylation of primary amines in the presence of secondary amines was also demonstrated.

Direct synthesis of secondary amines from alcohols and ammonia catalyzed by a ruthenium pincer complex - Balaraman, Ekambaram; Srimani, Dipankar; Diskin-Posner, Yael; Milstein, David (Catalysis Letters, 2015)
Efficient and selective direct synthesis of secondary amines from primary alcohols and ammonia with liberation of water has been achieved, with high turnover numbers and with no generation of waste. In case of benzylic alcohols, imines rather than amines are obtained. This atom economical, environmentally benign reaction is homogenously catalyzed by a well-defined bipyridine based Ru(II)-PNN pincer complex.
Keywords: Alcohol; Ammonia; Homogenous catalysis; Ru-pincer complex; Secondary amine